Probability analysis of rainfall and evolving Cropping system for Coimbatore - KULANDAIVELU, R. (MAUSAM, 1984)
The daily precipitation data of Coimbatore centre for a period of 70 years were computed for weekly totals by fitting incomplete gamma distribution. model in an IBM computer. The assured weekly rainfall amounts with different probability levels and the probability of receiving a given amount of rainfall were worked out and presented. The data indicate the likely commencement of rains, period of drought, length of growing season and end of growing season. Based on the assured rainfall at 50 percent probability level suitable cropping system was suggested for Coimbatore.